2005
DOI: 10.1074/jbc.m412434200
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Can Relieve Translational Repression of TOP mRNAs Elicited by Various Blocks along the Cell Cycle in a Glycogen Synthase Kinase-3- and S6-Kinase-independent Manner

Abstract: TOP mRNAs are translationally controlled by mitogenic, growth, and nutritional stimuli through a 5-terminal oligopyrimidine tract. Here we show that LiCl can alleviate the translational repression of these mRNAs when progression through the cell cycle is blocked at G 0 , G 1 /S, or G 2 /M phases in different cell lines and by various physiological and chemical means. This derepressive effect of LiCl does not involve resumption of cell division. Unlike its efficient derepressive effect in mitotically arrested c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…mTORC1 phosphorylation of its distinct targets has recently been shown to be differentially regulated in a cell-specific manner, which may be relevant to our observation of uncoupled 4E-BP1 and S6K1 regulation in response to diverse treatments, as noted below (10). The differential regulation of mTORC1 targets among different cell types may help explain why some investigators have reported decreased S6K1 activity during mitosis while others have reported increased signaling (6,59,64). In this regard, we note that not all mTORC1 targets are phosphorylated during mitosis.…”
Section: Resultsmentioning
confidence: 56%
“…mTORC1 phosphorylation of its distinct targets has recently been shown to be differentially regulated in a cell-specific manner, which may be relevant to our observation of uncoupled 4E-BP1 and S6K1 regulation in response to diverse treatments, as noted below (10). The differential regulation of mTORC1 targets among different cell types may help explain why some investigators have reported decreased S6K1 activity during mitosis while others have reported increased signaling (6,59,64). In this regard, we note that not all mTORC1 targets are phosphorylated during mitosis.…”
Section: Resultsmentioning
confidence: 56%
“…8B). Similar observations have been reported for nonneuronal cells and suggest that neither S6K1 nor S6K2 is required for the induction of S6 phosphorylation or the synthesis of 5ЈTOP-encoded proteins (36,46,48). Also important to consider is that we were not able to measure LTD-associated increases in S6 phosphorylation and EF1A levels in S6K1/S6K2 double knockout mice.…”
Section: Discussionmentioning
confidence: 57%
“…The fact that the translation of TOP mRNAs is repressed upon mitotic arrest by any means (48) and that rapamycin can completely block progression through the cell cycle, at least in some cell types (1,38,45), suggested a causal relationship between the effect of rapamycin on cell cycle progression and on TOP mRNAs. However, the lack of any correlation between the effects of rapamycin on the mitogenic activity of HEK 293 and 3T3-L1 cells (data not shown) on the one hand and on the translation efficiency of TOP mRNAs in these cell lines on the other hand ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TOP mRNAs are characterized by an oligopyrimidine tract at the 5Ј terminus and encode ribosomal proteins, elongation factors, and several other proteins associated with the assembly or function of the translational apparatus (34). The translation of these mRNAs is selectively repressed when proliferation of vertebrate cells is blocked at various phases of the cell cycle by a wide variety of physiological signals and pharmacological treatments or when they are amino acid starved (48). It has previously been shown that translational activation of TOP mRNAs is strictly dependent on the integrity of the phosphatidylinositol 3-kinase (PI3K) pathway (49,50).…”
mentioning
confidence: 99%